2017
DOI: 10.1021/acs.jpcc.7b05244
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Chain Alignment and Morphology in All-Polymer Blends Visualized Using 2D Polarization Fluorescence Imaging: Correlation to Power Conversion Efficiencies in Solar Cells

Abstract: All-polymer blends are promising materials for organic electronics. Their performance critically depends on the quality of mixing of the electron donor and acceptor polymers and on the local chain organization. We investigated spatially resolved photoluminescence properties of as-prepared and annealed blends of poly­[2,3-bis­(3-octyloxyphenyl)­quinoxaline-5,8-diyl-alt-thiophene-2,5-diyl] (TQ1) and poly­(N,N-bis-2-octyldodecyl-naphtalene-1,4,5,8-bisdicarboximide-2,6-diyl-alt-5,5–2,2-bithiophene) (N2200) using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This situation strongly necessitates the development of new morphological characterization tools, which can enhance the contrast between different polymer domains. In this context, several recent studies demonstrated the effectiveness of utilizing a series of other imaging tools including photoinduced force microscopy (PiFM), conductive atomic force microscopy (c-AFM), Kelvin probe force microscopy (KPFM), , and two-dimensional polarization imaging (2D POLIM) . The simultaneous application of multiple complementary approaches (e.g., X-ray scattering and imaging tools) can provide more detailed and more extensive morphological information on all-PSC blends across different length scales (from micro to nanometer scale).…”
Section: Discussionmentioning
confidence: 99%
“…This situation strongly necessitates the development of new morphological characterization tools, which can enhance the contrast between different polymer domains. In this context, several recent studies demonstrated the effectiveness of utilizing a series of other imaging tools including photoinduced force microscopy (PiFM), conductive atomic force microscopy (c-AFM), Kelvin probe force microscopy (KPFM), , and two-dimensional polarization imaging (2D POLIM) . The simultaneous application of multiple complementary approaches (e.g., X-ray scattering and imaging tools) can provide more detailed and more extensive morphological information on all-PSC blends across different length scales (from micro to nanometer scale).…”
Section: Discussionmentioning
confidence: 99%
“…One promising direction of molecular engineering is the design of conjugated materials having different sidechains to impart improved structural properties. It has been seen that the addi tion of a rigid sidechains along a conjugated backbone can impart favorable phase separation and miscibility properties [60,181]. There are also many studies that support the notion that the addition of methylated, fluorinated or alkylated side chains to ITIC can improve its deviceapplicable characteris tics [78,88,178,[182][183][184][185].…”
Section: Acceptor Designmentioning
confidence: 99%
“…This could be exploited to image structures or dynamic properties of soft materials receiving much attention recently, or biological materials. The polarization of emission has been used in the case of 2D polarization microscopy, defocused microscopy of single molecules, or microscopy of scattering of gold nanorods . The combination of polarized emission from nanorods and weak supramolecular interactions involving organic capping of QRs is evaluated as an imaging technique for the first time in this work.…”
Section: Introductionmentioning
confidence: 99%